CircFut8 Suppresses Bladder Cancer by Modulating SRSF9‐Dependent Pre‐mRNA Splicing - Weifeng Yang; Lv Yao; Lijun Wan; Changshui Zhuang (The Journal of Gene Medicine, 2026)
ABSTRACT Objective Circular RNAs (circRNAs) represent key regulators in cancer pathogenesis; however, their involvement in alternative splicing (AS) remains poorly understood. Methods Expression of circFut8 was detected in bladder cancer ( BC ) tissues/cell lines; RNA pull‐down, cross‐linking immunoprecipitation (CLIP) assays verified circFut8's interaction with splicing factor SRSF9. CircFut8 overexpression was performed to assess its effects on BC cell proliferation in vitro (CCK‐8, colony formation) and tumor growth in vivo (xenograft models), and its modulation of FUT8 pre‐mRNA splicing was analyzed. Results Here, we identify circFut8—a conserved exonic circRNA originating from FUT8 gene exon 3—as a BC tumor suppressor, which is significantly downregulated in BC tissues and cell lines, correlating with advanced tumor grade and invasion. Mechanistically, circFut8 competitively binds the splicing factor SRSF9, thereby modulating the inclusion/exclusion of exon 3 in FUT8 pre‐mRNA and promoting the production of the FUT8‐4 splice variant. Functional assays confirm that circFut8 overexpression inhibits BC proliferation in vitro and suppresses tumor growth in vivo, while RNA pull‐down and cross‐linking immunoprecipitation (CLIP) assays confirm its direct interaction with SRSF9. Conclusions Our findings unveil a novel circRNA‐mediated regulatory axis wherein circFut8 fine‐tunes pre‐mRNA splicing through competition with SRSF9, suggesting its potential as a candidate for further therapeutic exploration.